Pengaruh NPK terhadap Produktivitas dan Kualitas Sorgum (Sorghum bicolor) Varietas Mitting Tadda sebagai Pakan - Nani, Lusia R.T; ., Suprihati; Ama, Arnol T; Rengganis, Yacinta; Banjarnahor, Dina (JURNAL BUDIDAYA PERTANIAN, 2025)
Sorghum (Sorghum bicolor L. Moench) is one of the cereal plants that can be used as animal feed. “Miting Tadda” sorghum variety has the potential to be cultivated in Central Java, precisely in Getasan Sub-district. Currently, the optimal macronutrient recommendations including nitrogen (N), phosphorus (P), and potassium (K) for sorghum cultivation in Central Java are not yet known. The fertilizer dosage for sorghum plants that has been found in the literature is not specific to the Miting Tadda sorghum type and the type of soil in Getasan. This study aimed to determine the effect of various fertilizer doses on the productivity and quality of seeds and greens of Miting Tadda sorghum variety. The study was conducted at the Science Techno Park, Faculty of Agriculture and Business, Satya Wacana Christian University. This study used a Randomized Block Design (RBD) with 5 fertilizer dose treatments (g per plant), namely: without fertilizer, 2.44 N + 0.5 P₂O₅ + 0.45 K₂O, 3.69 N + 0.5 P₂O₅ + 0.45 K₂O, 4.89 N + 0.5 P₂O₅ + 0.45 K₂O, 6.08 N + 0.5 P₂O₅ + 0.45 K₂O. The experiment was conducted in 4 groups as replications so that there were 20 experimental units. The results showed that based on the results of the ANOVA test, there was no significant effect of the NPK fertilizer dose treatment in the range given in this study on the components of sorghum seed and forage productivity and the quality of sorghum seeds and forage was relatively the same in all treatments. The use of fertilizers in low doses or even without fertilizer can be an alternative in sorghum cultivation.